Ciencia, ideología y educación (2021)
In this essay, I argue that great ideologies can be conceived and propagated only if the appropriate material conditions are present; therefore, they are not predictable. In this article, I highlight the sine qua non conditions for the emergence of ideologies such as gender perspective and feminism. I show how, with the development of capitalism, the political struggle gradually lost its class character and was largely oriented towards sexuality issues. From my perspective, there is a plausible justification for the gender perspective as opposed to what happens with feminism.